2017
DOI: 10.1038/ncb3490
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic-reticulum-mediated microtubule alignment governs cytoplasmic streaming

Abstract: Cytoplasmic streaming refers to a collective movement of cytoplasm observed in many cell types. The mechanism of meiotic cytoplasmic streaming (MeiCS) in Caenorhabditis elegans zygotes is puzzling as the direction of the flow is not predefined by cell polarity and occasionally reverses. Here, we demonstrate that the endoplasmic reticulum (ER) network structure is required for the collective flow. Using a combination of RNAi, microscopy and image processing of C. elegans zygotes, we devise a theoretical model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…Our previous study suggested that a primary role of MeiCS is to increase the mobility of cortical granules for their efficient exocytosis at the meiotic anaphase I 20 . In contrast, the movement of SPCC is considered unfavourable for the cell as it may induce a contact between the oocyte chromosome and sperm chromosome before the oocyte meiosis 23 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study suggested that a primary role of MeiCS is to increase the mobility of cortical granules for their efficient exocytosis at the meiotic anaphase I 20 . In contrast, the movement of SPCC is considered unfavourable for the cell as it may induce a contact between the oocyte chromosome and sperm chromosome before the oocyte meiosis 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The nature of MeiCS is likely designed to move cortical granules efficiently while keeping the movement of SPCC minimum. The flow direction of MeiCS is biased along the short axes of the zygote and, thus, it does not effectively moves SPCC along the long axis 20 . In addition, MeiCS is not stable and stochastically changes the direction 20 , which also makes a long-distance movement difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations